S SYSTEM FOR DETERMINING RECOMMENDATIONS FOR BIRD'S NEST CONSTRUCTION LOCATION IN RIAU USING THE WEIGHTED PRODUCT METHOD - wahyuri, hafiz (Universitas Multi Data Palembang, 2024)
A very important activity in the bird industry is the construction of bird nests. The right location to build a whalet nest affects the productivity and success of the company. Therefore, in order to help the entrepreneur in making the right decision, a location recommendation for a whalet nest should be developed. The Weighted Product (WP) method is used to calculate and evaluate criteria relevant to the location of a whalet nest. These criteria include economic factors such as land costs and potential benefits, as well as the availability of natural resources and supporting infrastructure.